The effect of artificial lighting of cowsheds on the milk productivity of cows under the conditions of tethered housing - Dmytro Nosevych; Vasyl Kostenko; Maryna Kulish; Inna Subot (Тваринництво та технології харчових продуктів, 2022)
The relevance of this study is conditioned upon the need to establish the possibility of using artificial lighting to increase the productivity of cows with tethered maintenance. This paper is aimed at identifying the effect of adjustable lighting of the feed table with LED lamps on the dairy productivity of cows. The cowshed lighting was provided by the SmartAC (LRC) automatic control system. The research method was to analyse the dynamics of cow milk yield under controlled photoperiod conditions and the level of illumination of the room. Two groups of cows were formed: experimental cows were kept in an experimental cowshed with natural illumination of the feed table of 101±20.2 lx and artificial illumination of 202±19.9 lx, the control group was kept in a typical 2-row room for 100 heads, in which natural illumination feed table was 139±22.8 lx, artificial – 26±3.2 lx. The duration of the photoperiod was 16 hours, and the ratio between natural and artificial lighting depended on the astronomical length of the day. Milk productivity of cows was assessed according to the method of control milking. Milk yields were recorded one month before the installation of the experimental lighting system (in February) and for the next four months (from March to June). Before the installation of the experimental lighting system, the difference in milk yield of cows was not statistically significant. In the future, despite fluctuations in the amount of milk yield caused by feeding, the experimental group of cows exceeded the control group in terms of milk productivity. The advantage of the cows of the experimental group in terms of daily milk yield was from 2.3 kg in March to 5.8 kg (p<0.01) in May. During the period of maximum daylight hours (June), the effect of artificial lighting on the dairy productivity of cows was insignificant. It was noted that the increase in the preference of experimental cows for milk yield occurs over several months, and the positive impact of improved lighting of the feed table increases along with an increase in milk productivity on the farm. That is, the higher the feeding level, the greater the effect of lighting control. The obtained results were confirmed after the analysis of the productivity of analogue cows by age and lactation phase, selected from the experimental and control groups. The results of the study are of practical value for the improvement of lighting in cowsheds with tethered housing